Pemenuhan Pemenuhan Kriteria Smart Port Terhadap Eksisting Terminal 2 Pelabuhan Petikemas New Makassar - Nur Azisah; Muhammad Asdar; Chairul Paotonan (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2023)
Smart ports are an innovative solution for the world's port industry in the application of integrated technology and environmental sustainability to increase the efficiency and effectiveness of operational services. The concept of smart ports is usually widely adapted to container ports because most of the world's trade is carried by sea in containers. Terminal II of the New Makassar Container Port which is a new container port in Indonesia and is expected to develop into a gateway for world trade in Eastern Indonesia in order to improve the socio-economic region is required to innovate and keep abreast of world port trends. Therefore, to support Terminal II of the New Makassar Container Port to develop into a smart port, a study was conducted to determine the extent to which the port met the criteria for a smart port. In carrying out the research, direct observation and interview methods were used with selected respondents at Terminal II of the New Makassar Container Port. Based on the observation results, it was found that Terminal II of the New Makassar Container Port had fulfilled the productivity criteria in the operational domain and the safety and security management system criteria as well as the Integrated monitoring and optimization system.